آراء ابن خلدون التربوية ودرجة اتفاقها مع التربية الحديثة - تيقرين, حورية جميلة (جامعة الوادي - University of Eloued, 2022)
يهدف هذا البحث إلى تسليطالضوء على واحد من أعظم علماء التاريخ وواحد من رواد التربية، ومؤسسي علم الإجتماع، كما يهدف إلى تقديم شرحًا وافرًا عن آراء وتوجيهات هذا العالم بخصوص الفكر التربوي ومقارنته بالفكر التربوي الحديث، ومعرفة مدى التغير والتحول الذي طرأ على مبادئ الفكر التربوي عبر الزمن منذ عصر ابن خلدون إلى عصرنا هذا، وكذلك معرفة ما لإبن خلدون من دور فعّال في هذا المجال من خلال النظر في آرائه وافكاره وتأثيره علم التربية الحديث . Abstract: This research aims to shed light on one of the greatest scholars of history, one of the pioneers of education, and the founders of sociology. It also aims to provide an extensive explanation of the opinions and directions of this scholar regarding educational thought compared to modern educational thought and the degree of evolution inthe principles of the educational thought across time, since the era of IbnKhaldun to the present time.Moreover, the researcher tries to uncover IbnKhaldun's effective role in this field of education by presenting his views, ideas regarding modern pedagogy.
The educational views of Ibn Khaldoun and their degree of agreement with modern education
مقال
Keywords: ابن خلدون، الآراء التربوية، درجة الاتفاق، التربية الحديثة.; Ibn Khaldun, educational opinions, degree of agreement, modern education.